Towards the use of the coccolith vital effects in palaeoceanography: A field investigation during the middle Miocene in the SW Pacific Ocean. (June 2020) - Hermoso, Michaël; McClelland, Harry-Luke O.; Hirst, James S.; Minoletti, Fabrice; Bonifacie, Magali; Rickaby, Rosalind E.M.
Abstract: Recent culture studies of living coccolithophores have established a biogeochemical framework for the use of the geochemical compositions of their calcite biominerals as proxies in palaeoceanography. Yet, questions remain regarding the transferability of such experimental data to fossil coccoliths. Here we analysed the carbon and oxygen isotopic composition of Miocene coccoliths to assess the suitability of such data for reconstructing the past environment. We found that the oxygen isotopic compositions of the relatively small Noelaerhabdaceae coccoliths gathered in the 3–5 μm fractions appear to be a suitable material to derive temperatures after a correction for a constant vital offset of 0.8‰. The interpretation of the isotopic signal of the relatively large Coccolithales coccoliths (5–8 μm fractions) is more complex, but supports results from cultures. The expression of the carbon and oxygen vital effect in coccoliths appears to be limited during the so-called Miocene Climate Optimum (MCO), a period of relatively elevated atmospheric pCO2 . Subsequently, during the Miocene Climatic Transition (MCT; 14 Ma), which saw a decline in pCO2, large carbon and oxygen vital effects were expressed in coccolith calcite. This phenomenon predates the postulated " Late Miocene Threshold " by approximately 4 Ma, and cannot be reconciled as a temporally-synchronous nor localised feature. Furthermore, we observed a statistically significant correlation between the oxygen and carbon offsets of the small relative to large coccoliths (hence, the vital effect per se ) that is likely linked to variations in atmospheric CO2 . This biogeochemical correlation further supports a forcing of the environment on the cellular physiology (growth rate and utilisation of intracellular carbon) and ultimately the magnitude of isotopic vital effects in fossil coccoliths. Highlights: Size-specific carbon and oxygen isotopes are reported for coccoliths spanning the Miocene Climatic Transition (MCT). Coccoliths in different size classes show contrasting vital effects which are evaluated within an existing pCO2 framework. The observed correlation in Δ 18 O/Δ 13 C between small and large species may reflect a decline in CO2 through the MCT.